On the calculation of rectangular plates by the trigonometric series - Yessenbayeva, G.A.; Akhanov, F.M.; Makazhanova, T.Kh. (Bulletin of the Karaganda University. Mathematics Series, 2019)
The article is devoted to the question of applying the method of single trigonometric series to solving the plate bending problems. In this article the structure of this method is described, its main components are highlighted, the classical approach of calculating rectangular plates hinged supported on two parallel sides and with arbitrary boundary conditions on each of the other two sides is characterized. The mathematical apparatus of the method of single trigonometric series is presented in the volume necessary for calculating the plates. The detailed example of calculating a rectangular plate by the stated method is given. The article is focused mainly on students and undergraduates engaged in research work in the field of mechanics and applied mathematics.